2013
DOI: 10.6061/clinics/2013(01)oa06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal function and immune system cells in elderly individuals from São Paulo City

Abstract: OBJECTIVES:Both renal function and immune system function decline with age. Although controversial, a significant number of studies have shown that the decline in kidney function is associated with the worsening of the immune system. These findings are reinforced by the increased susceptibility to infections and deficient immunization coverage after vaccination both in patients with chronic renal disease and in elderly individuals. Our objective was to evaluate a non-institutionalized elderly population from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…The humoral immune response of the under studiedCKDpatients was affected in agreement with [36] that depended on B-Cells decreasing and death by apoptosis due to Uremia, thereby it causes a decreasing in immunoglobulins (Igs) levels production such as IgG, IgM and IgA especially in hemodialysis patients (HD) in agreement with [37,38] .…”
Section: Discussionsupporting
confidence: 72%
“…The humoral immune response of the under studiedCKDpatients was affected in agreement with [36] that depended on B-Cells decreasing and death by apoptosis due to Uremia, thereby it causes a decreasing in immunoglobulins (Igs) levels production such as IgG, IgM and IgA especially in hemodialysis patients (HD) in agreement with [37,38] .…”
Section: Discussionsupporting
confidence: 72%
“…So there are 5 stages of chronic kidney disease according to the American Kidney Foundation classification (G1-G5, K/DOQI clinical practice guidelines for chronic kidney disease: evaluation, classification, and stratification). Teixeira et al (2013) reported an investigation on whether there was a confirmed decline of kidney function which correlated with the changes of levels of CD4 + T, CD8 + T and B cells in older patients. It is possible to observe that G3a (GFR = 45-59 mL/min/1.73 m 2 ) under light to moderate chronic kidney insufficiency in accordance with the classification of The American Kidney Foundation was related to considerably lower median percentage of CD8 + Т-cells, while substantial distinctions were not discovered in regard to the percentage of CD4 + Т-cells, percentage of Вcells (CD19 + ) or correlations of CD4/CD8 between individuals with similar kidney functions.…”
Section: Introductionmentioning
confidence: 99%
“…The innate and adaptive immune responses are very well coordinated and tightly regulated. It is when this coordination and regulation fails, that diseases occur ( 2 , 3 , 5 , 6 ).…”
mentioning
confidence: 99%